Mangrove ecosystem service values and shrimp aquaculture in Can Gio Province, Vietnam - Sakchai McDonough; Gallardo, Wenresti G.; Dabbadie, Lionel; Yakupitiyage, Amararatne; Berg, Hakan; Nguyen Van Trai; RTG Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2012)
The valuation of wetlands often applies a monetary approach that may undermine the intrinsic values attached to a natural habitat. Applying a participatory stated preference method, ecosystem service values were mapped and assessed between subsistence mangrove users and shrimp farmer groups, contrasting the potential costs and benefits between intensive shrimp development and mangrove conservation efforts in Can Gio province, Vietnam. For both study groups, final choice selections, through group deliberations exhibited strong values for ecosystem services delivered at a hypothetical natural state (core area pre-interventionat45%, core area post-interventionat55%; buffer zone pre-interventionat65%, buffer zone post-intervention at 73%), whereby the respondents favoured ecosystem services at a natural scenario. Minimal values were placed on a hypothetical alternative shrimp development scenario (core area pre-interventionat18%, core area post-intervention at 9%; buffer zone pre-intervention at 12%, buffer zone post-intervention at 5%), whereby the respondents avoided the potential costs and benefits of intensive shrimp farming. Group debates between the respondents demonstrated that deliberation drew out a sense of altruism that superseded potential economic profits and a higher sense of awareness to intrinsic values, whereby certain ecosystem services were deemed irreplaceable. The study findings challenge how we use the concept of ecosystem services in economic valuation approaches and highlights new ways to incorporate the {u2018}unaccountable{u2019} aspects attached to nature.
A thesis submitted in partial fulfilment of the requirements for the degree of Masters of Science in Aquaculture and Aquatic Resources Management
Thesis (M.Sc.) - Asian Institute of Technology, 2012
Keywords: Mangrove ecology -- Vietnam -- Can Gio; Shrimp culture -- Vietnam -- Can Gio; Ecosystem management -- Vietnam -- Can Gio